2015
DOI: 10.1021/acs.iecr.5b01404
|View full text |Cite
|
Sign up to set email alerts
|

Speeding Up Chemisorption Analysis by Direct IR-Heat-Release Measurements (Infrasorp Technology): A Screening Alternative to Breakthrough Measurements

Abstract: In this study, a new innovative adsorption screening method, Infrasorp technology, is presented as a quick and efficient measurement tool for the determination of H 2 S adsorption capacity and compared to breakthrough measurements. Using zinc oxide nanoparticles and metal−organic framework materials, a clear correlation between those two techniques was found, showing the broad applicability of the method for different classes of materials and the potential of Infrasorp to be used as an alternative or prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…Instead, cooperative proximity effects likely lead to the anomalous observed increase in ammonia saturation uptake for M 2 Cl 2 BBTA. Using InfraSORP, a recently developed calorimetric technique, we further draw correlations between pore size and sorption kinetics. Finally, we show that MOF stability to ammonia or water, an oft-empirical parameter of fundamental and practical importance, correlates directly with the water exchange rates in homoleptic metal–aquo complexes, a fundamental property established decades ago that will serve as an easy guide for new MOF design in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, cooperative proximity effects likely lead to the anomalous observed increase in ammonia saturation uptake for M 2 Cl 2 BBTA. Using InfraSORP, a recently developed calorimetric technique, we further draw correlations between pore size and sorption kinetics. Finally, we show that MOF stability to ammonia or water, an oft-empirical parameter of fundamental and practical importance, correlates directly with the water exchange rates in homoleptic metal–aquo complexes, a fundamental property established decades ago that will serve as an easy guide for new MOF design in the future.…”
Section: Introductionmentioning
confidence: 99%
“…For DUT-134(Cu) based carpets, however, a remarkably high value of 14.6 mmol g À 1 could be achieved, almost six times higher than that of the bulk DUT-134 (Figure 8). The results were also validated by InfraSORP [30] measurements (for more details see Supporting Information). This value is approaching the capacity of MIL-53(Al)-TDC, a benchmark with the highest H 2 S adsorption (18.1 mmol g À 1 ) [31] ever reported for any adsorbent, but measured at a higher concentration of 5 vol % H 2 S in N 2 at 303 K. CPO-27(Ni) (12 mmol g À 1 at 1 bar H 2 S at 303 K) [32] is clearly out-…”
Section: Air Filtrationmentioning
confidence: 58%
“…Thus, the InfraSORP is substantially faster than common characterization techniques, e.g., analysis of smoke components by HPLC or GC/MS using a smoking machine, which can take up to several hours. The single‐port instrument is more versatile and can be used for a wide range of gases, thus also giving an insight into selective adsorption and chemisorption performance 14.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the specific integral of the thermal response curve can be correlated to the specific surface area and the amount of adsorbed test gas over a wide range of microporous materials because under measurement conditions (298 K, p butane = 1 bar) p / p 0 is close to 0.4 and thus in the plateau of a type I isotherm. Under these high coverage conditions, the heat of adsorption is almost constant and independent of the adsorbent 11–15. Limitations may be encountered for very small pore materials, where pore wall interactions are dominant even at p / p 0 = 0.4.…”
Section: Introductionmentioning
confidence: 99%